2012
DOI: 10.1103/physrevlett.109.115001
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Generation by the Rayleigh-Taylor Instability in Laser-Driven Planar Plastic Targets

Abstract: Magnetic fields generated by the Rayleigh-Taylor instability were measured in laser-accelerated planar foils using ultrafast proton radiography. Thin plastic foils were irradiated with ∼4-kJ, 2.5-ns laser pulses focused to an intensity of ∼10(14)  W/cm(2) on the OMEGA EP Laser System. Target modulations were seeded by laser nonuniformities and amplified during target acceleration by the Rayleigh-Taylor instability. The experimental data show the hydrodynamic evolution of the target and MG-level magnetic fields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 27 publications
(32 reference statements)
2
44
0
Order By: Relevance
“…Maximal field strengths up to 2 MG were inferred from path-integrated measurements. Gao et al [27] also considered a 25 µm thick foil and found sub-MG fields; the foil stayed unbroken, suggesting that the fastest field growth was attained in the late, highly nonlinear stage of RTI.…”
Section: Comparison With Previously Published Experimental and Theorementioning
confidence: 99%
See 3 more Smart Citations
“…Maximal field strengths up to 2 MG were inferred from path-integrated measurements. Gao et al [27] also considered a 25 µm thick foil and found sub-MG fields; the foil stayed unbroken, suggesting that the fastest field growth was attained in the late, highly nonlinear stage of RTI.…”
Section: Comparison With Previously Published Experimental and Theorementioning
confidence: 99%
“…The target proposed by Nishiguchi is thinner and is continuously driven by a much stronger laser source. The laser intensity used by Nishiguchi was a constant 2 × 10 15 W cm −2 , while the laser drives used in experiments were weaker and lasted only for a short amount of time (9 × 10 14 W cm −2 for 1 ns in [1]; 4 × 10 14 for 2 ns in [3,27]). Although [2] does not provide the effective acceleration value, assuming a 2 MG magnetic field and a few micron thick interface, we can use the results shown in his Fig.…”
Section: /2mentioning
confidence: 99%
See 2 more Smart Citations
“…These fields strongly affect electron transport by suppressing the cross-field thermal conductivity (Braginskii 1965) and are thus key to understanding a range of laser-plasma interactions, including ongoing efforts to achieve controlled inertial confinement fusion (Glenzer et al 1999;Lindl et al 2004;Nilson et al 2006;Froula et al 2007;Li et al 2007a,b;Schurtz et al 2007;Froula et al 2009;Li et al 2009Li et al , 2013. Of special importance in such contexts is the role transport effects might play in driving instabilities, especially given that such instabilities are themselves often candidate mechanisms for producing the self-generated field (Weibel 1959;Tidman & Shanny 1974;Bol'shov et al 1974;Ogasawara et al 1980;Haines 1981;Bissell et al 2010Bissell et al , 2012Gao et al 2012;Manuel et al 2013).…”
Section: Introductionmentioning
confidence: 99%